Annual adult health screening: barriers, challenges and effectiveness - Al Yamani, Abrar A.; Mahnshi, Fahad A.; Alkhalifah, Abdullah A.; Alsawadi, Abdullah M.; Alnefaie, Bader O.; Alzahrani, Hussam S.; Kutbi, Mutasem S.; Bukhari, Amro A.; AlQattan, Turki M.; Tounsi, Majid T.; Alharbi, Rayan A. (International Journal Of Community Medicine And Public Health, 2021)
Although it has been well-established that screening for early detection and intervention practices has been associated with favorable outcomes, there have been many concerns about the potential of these approaches to cause harm to the patients. In addition, evidence also shows some associated barriers and challenges to these approaches that need to be considered by healthcare authorities when planning for such approaches. The present literature review discusses annual adult health screening programs' effectiveness, barriers, and challenges. There is no doubt that these screening programs can help identify undiagnosed disorders among many patients with various conditions, like diabetes mellitus, hypertension, and different cancers. Moreover, the effectiveness of these screening programs can be best highlighted by the premarital screening program in Saudi Arabia, which targets high-risk couples for developing certain conditions and infections. However, it should be noted that there are many barriers and challenges to conducting health screening campaigns, like cultural and economic factors. Other challenges might also include the rates of false-positive tests, overdiagnosis, and knowledge about the screening programs.